Peran Guru Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia Di Kelas XI SMKN 9 Medan - Yesli May Veronika Saragih; Christin Agustina Purba; Sartika Sari (elt, 2023)
Motivation is the drive to do an action or work that is influenced by internal factors and external factors. One of the external factors is the teacher. Teachers are the main success factor in the teaching and learning process. Teachers have a crucial role in determining the quality of learning that is carried out. The purpose of this research is to find out how the learning motivation of students in class XI SMKN 9 Medan and to find out the role of teachers in increasing student learning motivation in Indonesian language subjects in class XI SMKN 9 Medan. The research method used is descriptive qualitative research method. The results showed that student learning motivation in Indonesian language subjects was very much considered by teachers at SMKN 9 Medan and almost evenly the enthusiasm of students was very high in learning Indonesian. Because the Indonesian learning process is not monotonous and not boring for students. The role of teachers in increasing student learning motivation in Indonesian language subjects in class XI SMKN 9 Medan is that teachers act as motivators not only as educators but also as parents with the aim of knowing students' interests and motivation. Teachers conduct assessments to each student to determine learning motivation and student learning achievement periodically.